Facile discovery of a therapeutic agent for NK-mediated synergistic antitumor effects using a patient-derived 3D platform. (23rd December 2021) - Lee, Young Eun; Yuk, Chae Min; Lee, Minseok; Han, Ki-Cheol; Jun, Eunsung; Kim, Tae Sung; Ku, Ja-Lok; Im, Sung G.; Lee, Eunjung; Jang, Mihue
Abstract : 3D tumor spheroid/NK co-culture platform facilitates the discovery of a small drug, C19, for synergistic NK-mediated cytolysis against pancreatic cancer patient-derived cancer spheroid. Abstract : Despite the essential roles of natural killer (NK) cells in cancer treatment, the physical barrier and biological cues of the tumor microenvironment (TME) may induce NK cell dysfunction, causing their poor infiltration into tumors. The currently available two-dimensional (2D) cancer-NK co-culture systems hardly represent the characteristics of TME and are not suitable for tracking the infiltration of immune cells and assessing the efficacy of immunotherapy. This study aims to monitor NK-mediated cancer cell killing using a polymer thin film-based, 3D assay platform that contains highly tumorigenic cancer spheroids. A poly(cyclohexyl methacrylate) (pCHMA)-coated surface enables the generation of tumorigenic spheroids from pancreatic cancer patient-derived cancer cells, showing considerable amounts of extracellular matrix (ECM) proteins and cancer stem cell (CSC)-like characteristics. The 3D spheroid-based assay platform allows rapid discovery of a therapeutic agent for synergistic NK-mediated cytotoxicity through imaging-based high-content screening. In detail, the small molecule C19, known as a multi-epithelial–mesenchymal transition pathway inhibitor, is shown to enhance NK activation and infiltration via modulation of the ECM, resulting in synergistic cytotoxicity against cancer spheroids. This 3D biomimetic co-culture assay platform provides promising applications for predicting patient-specific responses to immunotherapy through advanced therapeutic combinations involving a chemical drug and immune cells.